PENGEMBANGAN INSTRUMEN PENGUKURAN BERPIKIR KRITIS DALAM DISKUSI SISWA KELAS X DI SMK NEGERI 1 KASIHAN - Fernando, Dito (KARMAWIBANGGA Historical Studies Journal, 2025)
This research aims to find out: (1) Knowing the development of critical thinking instruments in the discussion of class X students of SMK N 1 Kasihan. (2) Knowing the quality of the instrument for measuring students' critical thinking. This research is an R&D (Research and Development) research. R&D research is a research method used to develop certain products. In this study, researchers developed a measurement instrument for critical thinking in student discussions. The development model in this research is ADDIE which uses several steps, namely (Analysis, Design, Development, Implementation, and Evaluation). The results of this study resulted in: (1) instrument development through validation by three validators who have a high average with a score of 0.966%. after being tested on students showed that the average critical thinking power was high with an average of 73.90%. (2) the results of the validity of the instrument stated that each item of the instrument was declared valid, the reliability results showed that the instrument was reliable with a score of 0.896, the feasibility test results on each item showed that this instrument was feasible with a feasibility score of 73.96%, and the results of the critical thinking power test showed a high score with an average of 73.90%.